Estudo da síntese de biodiesel a partir do óleo de girassol refinado e etanol anidro - Gandolfi, Marcus Vinícius Cavalcanti (2008)
Considering the operation of non-renewable sources of energy and environmental impacts caused by the misuse of these, the demand for renewable alternatives is a matter of survival for humanity. Thus, biodiesel is a viable solution to replace or reduce the consumption of mineral diesel oil. For the southern region of Brazil, studies indicate the viability of sunflower oil as raw material for the synthesis of biodiesel. The use of ethanol it becomes advantageous in the synthesis of biodiesel because it produced in large scale in the country to be mixed with gasoline. Therefore, taking into account the national and regional scenarios, this thesis aimed to study the transesterification of refined sunflower oil with ethanol for the production of biodiesel, using as the basic catalyst sodium hydroxide (NaOH) and potassium (KOH ) and methoxy sodium (CH3ONa). The influence of varying temperature, molar ratio of oil: alcohol and amount of catalyst were also studied. For the same conditions of reaction, the levels of conversion achieved in the presence of NaOH were greater than those observed with CH3ONa and KOH, respectively. It was found that the catalyst NaOH showed the best performance, when one considers the overall average conversion, the temperature of 60 ° C and molar ratio of oil: alcohol of 1:9 in volume 1% m / m. There was also that the use of higher quantities of catalyst, the temperature and molar ratio oil: high alcohol, tend to favor an emulsification of ethyl ester formed with intermediaries, diglicerídeos (DG) and monoglicerídeos (MG), decreasing the concentration of esters in the mixture, or to the advantage of the saponification reaction of triglycerides (TG), and the possibility of forming an emulsion of soap with the esters and TG. From the data obtained the reaction was possible to adjust a kinetic expression for the overall reaction and to estimate the apparent activation energy. Thus, the model for a reaction of second order (Law of speed) was the one with the linear correlation coefficients higher for all conditions studied. This model was therefore the best fit to the experimental data. The apparent activation energy for the reaction in the presence of NaOH (7.85 kcal / mol) is lower than that observed when using the methoxy sodium (15.6 kcal / mol) and KOH (23.9 kcal / mol ), this value is close to the value for the transesterification of sunflower oil with methanol (6.965 kcal / mol). Therefore, from the results achieved in this study, it becomes clear the importance of determining the optimal operating conditions for the reaction of transesterification of sunflower oil with ethanol.